Diagnosis, clinical features, and mortality risk factors in a Chinese cohort with pulmonary mucormycosis - Junjun Wan; Teng Liu; Fang Li; Shaohua Xu (PLoS ONE, 2025)
Background Pulmonary mucormycosis is a rare and often fatal fungal infection. Identifying high-risk factors for pulmonary mucormycosis holds the potential to improve patient outcomes. This study aimed to identify the clinical characteristics and risk factors associated with pulmonary mucormycosis outcomes in a Chinese cohort. Materials and methods A retrospective analysis was conducted on 37 patients diagnosed with pulmonary mucormycosis, focusing on clinical records, laboratory findings, and computed tomography (CT) imaging. Diagnosis was primarily based on histopathology or next-generation sequencing. Results The median age of the patients was 55 years, and the most common underlying conditions were hematological malignancies, diabetes, and organ transplantation. Imaging frequently revealed bilateral lung involvement with ground-glass opacities and nodular lesions. The overall mortality rate was 29.7%, with significant risk factors for 90-day mortality including hypertension (Hazard Ratio [HR] = 3.36, 95% Confidence Interval [CI] = 1.01–11.12, P = 0.048), organ transplantation (HR = 4.93, 95% CI = 1.48–16.4, P = 0.009), and immunosuppression (HR = 8.83, 95% CI = 1.13–69.14, P = 0.038). Conclusions Early suspicion and timely diagnostic measures, such as biopsy or metagenomic sequencing, are crucial for improving patient outcomes. These findings underscore the importance of recognizing and managing pulmonary mucormycosis in high-risk populations.